(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine: (1) the direct influence of work – life balance on female teacher perfomance, (2) the direct influence of workload on female teacher perfomance, (3) the direct influence of work environment on female teacher perfomance, (4) the influence of work – life balance on female teacher perfomance mediated by work stress, (5) the influence of workload on female teacher perfomance mediated by work stress, (6) the influence of work environment on female teacher perfomance mediated by work stress. The sampling technique used non – probability sampling. Data were obtained by distributing questionnaires about work – life balance, workload, work environment, work stress, and teacher perfomance to 74 married female teachers in Senior High Schools in Golewa Raya District. Data analysis was conducted using SmartPLS 4.0. The result of the study indicate that: (1) work – life balance directly positively influences female teacher perfomance, (2) workload directly negatively influences female teacher perfomance, (3) work environment positively influences female teacher perfomance, (4) work – life balance does not to influence female teacher perfomance mediated by work stress, (5) workload does not influence female teacher perfomance mediated by work stress, (6) work environment does not influence female teacher perfomance mediated by work stress.